Pembelajaran IPS di Luar Kelas - Szauli Putra , Berkah Adityo (Orasi: Jurnal Ilmu Politik dan Sosial, 2024)
The background of this research is social studies learning outside the classroom. The purpose of this research is to find out how the implementation of social studies learning outside the classroom at SMP Negeri 13 North Bengkulu. The research informants are Social studies teacher. The research method in this research is qualitative method of case study type. Instrument and Technique data collection techniques are observation, interview,documentation. Data analysis techniques are data reduction, data presentation, conclusion drawing. As for the results The conclusion of this research is the application of IPS learning strategy outside the classroom can make students active and enthusiastic in the learning process. And enthusiastic in the learning process. This can be seen in the results of researchers' interviews with social studies teachers at SMP Negeri 13 North Bengkulu who said students very enthusiastic about the learning process outside the classroom compared to learning in the classroom.